The Translation of Subject Pronoun I from English into Balinese in the Novel The Little Prince and Raja Cenik - Ariani, Ni Made (e-Journal of Linguistics; Vol 17 No 1 (2023): ejl-JanuaryDO - 10.24843/e-jl.2023.v17.i01.p02, 2022)
Balinese language has various varieties for its subject pronoun I. Investigating whether the translator presents these varieties when translating the English subject pronoun I into Balinese using the novel The Little Prince and its Balinese translation Raja Cenik is the focus of this study. As the finding, the translator utilizes three different lexicons in translating the English subject pronoun I into Balinese. These varieties include Icang, Titiang and Gelah. The utilization of these three lexicons depends on the social status of the speakers and the interlocutors. Balinese language possesses a number of different linguistic registers. Each of the register addresses the social status of the speakers and the interlocutors. The finding of this study shows that culture and language are intricately interwoven to each other in the translation process.